The Effectiveness of the Spinning Wheel Game toward Students' Speaking Skill - Bagus Dynasiar; Husni Mubarok (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to appraise the conclusiveness of the Spinning Wheel game in enhancing the descriptive text-speaking skills of seventh-grade students during the 2024-2025 academic yearat Junior High School Muhammadiyah 3 Bangsri. The study adopts a quasi-experimental design, incorporating both a pre-test and a post-test for control groups and both the experimental. The experimental group will participate in activities involving the Spinning Wheel Game, while the control group will follow conventional teaching methods. The sample comprises seventh-grade students selected through non-probability sampling and intentional selection techniques. Data collection involves administering pretests and posttests to both groups. The results from normality and homogeneity tests for the pretest and posttest reveal that the data from both groups is homogeneous and normally distributed. The homogeneity is evaluated using the Anova test, and the normality is assessed through the Kolmogorov-Smirnov test. Upon analyzing the posttest scores of both groups, the significance value (2-tailed) was found to be 0.000, which is below the significance threshold of 0.05 (0.000 < 0.05). The results reveal that students in the experimental group, who took part in the Spinning Wheel Game, significantly excelled compared to their peers in the control group, who did not experience the game. Thus, the alternative hypothesis (Ha) is confirmed and the null hypothesis (H0) is rejected. This outcome demonstrates how well the Spinning Wheel Game works to improve seventh-grade students' descriptive text-speaking abilities.